THE RELATIONSHIP BETWEEN PARENTAL COMMUNICATION AND EMOTIONAL REGULATION IN ADOLESCENTS AGED 13-15 YEARS: A STUDY AT MTS AL KHOLAFIYAH TEKUNG,LUMAJANG REGENCY - Ike Nia Permata Bunda; Tutik Hidayati; Sri wahyuningsih (Lppm Unan, 2026)
Background: Adolescents aged 13–15 years are in a phase of rapid emotional development, requiring strong emotional regulation skills to avoid risky behavior. Warm, open, and responsive parental communication is a crucial factor in helping adolescents understand and manage their emotions more healthily. However, poor communication within the family often leads to adolescents experiencing difficulty regulating their emotions. With this background in mind, the researcher aimed to explore the